Simulation of natural ventilation system in chemistry laboratory of faculty chemical and natural resources engineering lab building - Ruhama, Walled (2010)
The performance of natural ventilation in buildings is often being performed by using computational fluid dynamics (CFD) software, who‟s gaining its popularity recently. The main goal for this research is to improve the ventilation system by comparing the performance for the current ventilation system and the modified ventilation system. The air distribution is being focused more in order to predict the performance. Chemistry lab of faculty Chemical and natural resource engineering laboratory building is used as the model. Large Eddy Simulation (LES) is applied to estimate the air distribution of ventilation system in the cubic room of chemistry lab. The ambient temperature and pressure are used to be substitute into numerical model. The numerical result that obtained from the simulation is compared with the existing experimental data which the air change rate of laboratory must be at least 30% less than the standard which the standard value of ACH is in the range of 6 to 12 ACH. As the result, the modified ventilation system is showing the optimum of air change rate inside the chemistry lab. The air change rate for a person inside the laboratory is 9 ACH compared to current ventilation which that the value is over the standard value. As the conclusion, the modified ventilation system of the chemistry lab enhances the performance of the ventilation.